Branding and marketing in automobile industry of Bangladesh: focusing on Ford and Jeep- brands distributed by Anwar Group automobile division - Ashraf, Zayed (Brac University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2021.